Review of Gyucha A. & Parkinson W. A. (eds.), First Kings of Europe. From Farmers to Rulers in Prehistoric Southeastern Europe. - Heilmann, Daniela (Ex Novo: Journal of Archaeology, 2024)
Review of Gyucha A. & Parkinson W. A. (eds.), First Kings of Europe. From Farmers to Rulers in Prehistoric Southeastern Europe. Cotsen Institute of Archaeological Press, The Field Museum of Natural History. Los Angeles, 2022. Hardcover, 235 pages, ISBN 781950446247